Simulation in surgical training: Prospective cohort study of access, attitudes and experiences of surgical trainees in the UK and Ireland. (July 2019) - Nicholas, R.; Humm, G.; MacLeod, K.E.; Bathla, S.; Horgan, A.; Nally, D.M.; Glasbey, J.; Clements, J.M.; Fleming, C.; Mohan, H.M.
Abstract: Background: Surgical training is evolving, and simulation is becoming more important as a way to expedite the early learning curve and augment surgical techniques. With novel technology, and innovation, major changes are possible in how surgeons are trained. The integration of these concepts into the surgical curriculum may drive up educational standards and enhance patient safety. This survey sought to determine surgical trainees views on the current place of simulation in surgical training and explore their vision for the future. Material and methods: This is a prospective, questionnaire-based cross-sectional study by *** and the ***, England. Surgical trainees were surveyed about their experiences of simulation during their training through an electronic questionnaire distributed in the UK and Republic of Ireland through mailing lists of RCS and ***. Quantitative and qualitative research methodology was used. Results: Of 462 surveys submitted, a total of 323 were fully completed and included in the analysis. Core Surgical Trainees represented 28.4% of respondents. The vast majority of respondents (98.9%) considered that simulation training was important, however 55.0% felt it was delivered inadequately. 86.2% wanted greater access to simulation training: Less than half of respondents had access to simulation training at their current place of work or had simulation incorporated into their formal teaching programme (42.4% and 41.6% respectively). Conclusion: This study highlights the importance of simulation to trainees. Delivery and accessibility of simulation training varies widely. We highlight areas for improvement and best practice. In a culture of accountability, where patient safety is our highest priority, a "see one, do one, teach one" approach to training is no longer appropriate; instead we must utilise available simulation tools to augment learning. Highlights: Simulation is important – 98.9% of our respondents considered simulation training important. It is sought after by trainees but over half of our respondents felt it was inadequate. There is variability in delivery of simulation training - nearly half of respondents had no access or unclear access. Improving simulation training will enable better surgical training. Simulation training will enhance patient safety.